From tropical wetlands to pastures on the coast of the gulf of Mexico - Moreno-Casasola, P.; López Rosas, H.; Rodríguez-Medina, K. (Pastos, 2014)
Animal husbandry in Mexico began with the arrival of the Spaniards and the creation of New Spain. It changed significantly in the middle of the 20th century with the introduction of the Zebu breed of cattle and improved pastures. From the beginning, wetlands were used for cattle grazing, and we describe the transformations that occur in grazed wetlands that convert them into flooded pastures. The degree of impact depends on the number of cows, the time they are in the wetland, and modifications to hydroperiod and vegetation. We describe the changes in the level of flooding, the soil characteristics (organic matter, water retention, bulk density, pH, micro- and macronutrients) and floristic composition, and how all this affects the environmental services produced by wetlands. With the introduction of cattle breeds tolerant oftropical environments, mainly Zebu cattle, and of exotic forage grasses that can grow in wetlands, the impact has increased. These grasses drastically alter the environment (water and soil) and can become invasive. Therefore there is a gradient of transformation from wetlands with no cattle impact, to those with slight changes that continue to function as wetlands, and finally to heavily transformed wetlands. Management based on low livestock intensity maintains the functions and environmental services provided by wetlands while constituting a sustainable economic activity that permits theseecosystems to be preserved.